Relaciones interpersonal y su aporte en el clima laboral de la secretaria de la Unidad Educativa 4 de Mayo - Vera Aviles, Kaina Lissethe (2021)
When developing this investigation and proceeding with the case study, we noted that there is no link in the interpersonal relationship and its contribution to the work environment of the secretary of the educational unit May 4, where it was possible to verify that the administrative areas do not have a model of works where non-aggression policies could be created or simply a guide that addresses conflicts that may exist within the institution for any reason, we also apply the inductive method and as a data collection measure in an interview with the secretary of the institution and There, corroborate some design to find results and expose the deficits within the administrative area, however we must progressively improve the levels of work such as requests for grades. At the end of the entire process, there were many answers to different questions and the expected results were obtained from the Educational Unit May 4, however, we must give prior recommendations to progressively improve the levels of computer knowledge in the secretariats so that they can use new tools technological, all order to make the processes of administrative function and storage of information more feasible for the student. In conclusion, with respect to this research we find that if the institution provides digital and human resources to the institution, but also the constant training of technological tools to the secretaries that each day supply the needs of the users and therefore must be strengthened. Hence they make it known that the institution